Estudio semiótico de la relación entre estilo de comunicación y liderazgo: el caso del presidente Alejandro Toledo - Brown Gutiérrez, Ofelia (2003)
Through semiotic analysis, it is possible to know the symbology that a subject makes of his interpretation of the relations with the universe. This study is a first approach to the analysis of the symbolic world of Alejandro Toledo, expressed in his verbal and non-verbal language. It has sought to establish the relationships between leadership and communication style, as well as the role played by administrative language in the exercise of authority and power. To that end, fragments of the president's speeches have been analysed, from the pre-electoral phase to July 2003, and from the constants found, it has been possible to deduce its symbology and identify those aspects that affect the perception that citizens have of it.